Pengembangan Sistem Informasi Agenda Rapat Kecamatan (SIARKE) Menggunakan Metode Prototype (Studi Kasus Kecamatan Tulung Selapan) - Ike Sari; Novri Hadinata (Teknik Komputer Politeknik Negeri Sriwijaya, 2023)
The meeting agenda is an effort made by many parties in managing their activities, both individually and in groups. However, in terms of administration for staff and speed of information for leaders regarding the meeting agenda, there are still obstacles, including meeting files that accumulate so that it is difficult to find minutes quickly, leaders have difficulty seeing meeting agenda information because it is conveyed through the blackboard in the workspace. The purpose of this research is to build an information system on the village meeting agenda using the prototyping method with a case study at the Tulung Selapan sub-district office which includes the stages of listen to customer, build/revise mock-up, and customer tes-drives mock-up. The conclusion from the research results where the system development with a prototype description shows that the system owner has a clear picture of the system being built. The Regional Meeting Agenda Information System (SIARKE) can help sub-districts improve the effectiveness and performance of employees in managing meeting agenda data quickly.